Identification of two different mutations in the PDS gene in an inbred family with Pendred syndrome. Issue 6 (1st June 1999) - Coucke, P J; Van Hauwe, P; Everett, L A; Demirhan, O; Kabakkaya, Y; Dietrich, N L; Smith, R J H; Coyle, E; Reardon, W; Trembath, R; Willems, P J; Green, E D; et al.
Abstract : Recently the gene responsible for Pendred syndrome (PDS) was isolated and several mutations in the PDS gene have been identified in Pendred patients. Here we report the occurrence of two different PDS mutations in an extended inbred Turkish family. The majority of patients in this family are homozygous for a splice site mutation (1143-2A→G) affecting the 3′ splice site consensus sequence of intron 7. However, two affected sibs with non-consanguineous parents are compound heterozygotes for the splice site mutation and a missense mutation (1558T→G), substituting an evolutionarily conserved amino acid. The latter mutation has been found previously in two Pendred families originating from The Netherlands, indicating that the 1558T→G mutation may be a common mutation.